Refractory asthma in the UK: cross-sectional findings from a UK multicentre registry - Heaney, Liam G (BMJ Group, 2010)
INTRODUCTION: Refractory asthma represents a significant unmet clinical need where the evidence base for the assessment and therapeutic management is limited. The British Thoracic Society (BTS) Difficult Asthma Network has established an online National Registry to standardise specialist UK difficult asthma services and to facilitate research into the assessment and clinical management of difficult asthma. METHODS: Data from 382 well characterised patients, who fulfilled the American Thoracic Society definition for refractory asthma attending four specialist UK centres—Royal Brompton Hospital, London, Glenfield Hospital, Leicester, University Hospital of South Manchester and Belfast City Hospital—were used to compare patient demographics, disease characteristics and healthcare utilisation. RESULTS: Many demographic variables including gender, ethnicity and smoking prevalence were similar in UK centres and consistent with other published cohorts of refractory asthma. However, multiple demographic factors such as employment, family history, atopy prevalence, lung function, rates of hospital admission/unscheduled healthcare visits and medication usage were different from published data and significantly different between UK centres. General linear modelling with unscheduled healthcare visits, rescue oral steroids and hospital admissions as dependent variables all identified a significant association with clinical centre; different associations were identified when centre was not included as a factor. CONCLUSION: Whilst there are similarities in UK patients with refractory asthma consistent with other comparable published cohorts, there are also differences, which may reflect different patient populations. These differences in important population characteristics were also identified within different UK specialist centres. Pooling multicentre data on subjects with refractory asthma may miss important differences and potentially confound attempts to phenotype this population.